Petrogênese dos Stocks Mocambo e Frutuoso, Domínio Macururé, Sistema Orogênico Sergipano - Oliveira, Illana Rocha (2020)
The Mocambo (SM) and Frutuoso (SF) stocks, both with approximately 3 km2 , have elongated shapes and are intrusive in the metasediments of the central-eastern sector of the Macururé Domain (DM). The stock rocks have magmatic and tectonic foliations with general orientation NE-SW, parallel to those found in the metasedimentary host rocks. The U-PbSHRIMP age of 614 ± 7 Ma is interpreted as the age of crystallization of the SM rocks. The SM is composed of quartz diorites and quartz monzodiorites. SF rocks are quartz porphyritic diorites. Mafic enclaves (ME) of different types occur in these stocks. In the SF, a swarm of polygenic enclaves that correspond to diorites was observed. The presence of enclave and igneous cooling textures in these rocks indicates that at least two distinct magmas coexisted in the magmatic chamber, a hot mafic magma, and a colder felsic magma. The punctual chemical analysis revealed that the plagioclase crystals of these rocks are oligoclase and albite. The microcline has compositions close to the pure pole of the Or. The biotia is primary and is rebalanced. In SF and its enclaves, the calcium amphibole occurs associated with biotite crystals, and the data indicate that these crystallized at average pressures of 7.0 Kbar, corresponding to depths of 26 km, and in a high fO2 environment. The presence of a magmatic epidote also suggests crystallization at high pressures. Geochemical data indicate that SF and ME rocks are essentially metaluminous, while in SM they are metaluminous to weakly peraluminous. All rocks studied are magnesian and have an affinity with the rocks of the shoshonitic association. The multielement and REE patterns are similar in their geometries and Harker diagrams exhibit strong alignment, suggesting genetic correlation. The enrichment of LREE in relation to HREE and the depletion of Nb, Ta, Ti are compatible with rocks that originated from magmas with arc signature. The results obtained using major elements and trace, show that these rocks exhibit typical signatures of potassium rocks generated in a continental arc environment and had controlled evolution by fractional crystallization and mixture of magmas. Trace element ratios indicate that the source of these magmas may be associated with the enriched lithospheric mantle (metasomatized) below a subduction zone. Additionally, it suggests that the Mocambo stock represents an intrusion that was emplaced in an early to syn-collisional stage in relation to the Brasilian orogeny, and absorbed part of this deformation.